2000
DOI: 10.1016/s1097-2765(00)80246-4
|View full text |Cite
|
Sign up to set email alerts
|

MEX-5 and MEX-6 Function to Establish Soma/Germline Asymmetry in Early C. elegans Embryos

Abstract: An asymmetrical network of cortically localized PAR proteins forms shortly after fertilization of the C. elegans egg. This network is required for subsequent asymmetries in the expression patterns of several proteins that are encoded by nonlocalized, maternally expressed mRNAs. We provide evidence that two nearly identical genes, mex-5 and mex-6, link PAR asymmetry to those subsequent protein asymmetries. MEX-5 is a novel, cytoplasmic protein that is localized through PAR activities to the anterior pole of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
349
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(368 citation statements)
references
References 48 publications
16
349
1
2
Order By: Relevance
“…Mammalian TIS11-like zinc-finger-containing proteins have been shown to function either as transcription factors or RNA-binding proteins (Taylor et al 1996;Worthington et al 2002). Several C. elegans genes encoding proteins with TIS11-like zinc-finger domains have been described, including pie-1, mex-1, pos-1, mex-5, and mex-6, all of which are involved in early blastomere cellfate determination and germline development (Mello et al 1996;Guedes and Priess 1997;Tabara et al 1999;Schubert et al 2000). In addition, the recently identified TIS11-like proteins OMA-1, OMA-2, and OMA-3 are redundantly required for prophase progression during oocyte maturation (Detwiler et al 2001;Shimada et al 2002).…”
Section: Identification Of Mutations In the C Elegans Gla-3 Genementioning
confidence: 99%
“…Mammalian TIS11-like zinc-finger-containing proteins have been shown to function either as transcription factors or RNA-binding proteins (Taylor et al 1996;Worthington et al 2002). Several C. elegans genes encoding proteins with TIS11-like zinc-finger domains have been described, including pie-1, mex-1, pos-1, mex-5, and mex-6, all of which are involved in early blastomere cellfate determination and germline development (Mello et al 1996;Guedes and Priess 1997;Tabara et al 1999;Schubert et al 2000). In addition, the recently identified TIS11-like proteins OMA-1, OMA-2, and OMA-3 are redundantly required for prophase progression during oocyte maturation (Detwiler et al 2001;Shimada et al 2002).…”
Section: Identification Of Mutations In the C Elegans Gla-3 Genementioning
confidence: 99%
“…These effects have suggested that establishment of anterior and posterior PAR domains depends on antagonistic interactions between the PAR-3/PAR-6/PKC-3 complex in the anterior and PAR-2 in the posterior. In contrast, mutations in par-1, mex-5 and mex-6 were reported not to affect PAR localization in the zygote (Etemad-Moghadam et al, 1995;Boyd et al, 1996;Tabuse et al, 1998;Hung and Kemphues, 1999;Schubert et al, 2000). These mutations, however, have a dramatic effect on the distribution of several cell fate regulators.…”
Section: Introductionmentioning
confidence: 99%
“…PAR-1 in turn is required for asymmetric spindle positioning and for the asymmetric localization of several developmental regulators . PAR-1 exerts its influence on developmental regulators through MEX-5 and MEX-6, two redundant cytoplasmic CCCH finger proteins (Schubert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases where nucleotide sequence is highly conserved, RNAi with a single trigger molecule can target multiple family members (e.g., Colombo et al, 2003). If the number of family members is small, it is possible to reveal redundancies by double or triple knockout or knockdown (e.g., Schubert et al, 2000; Gotta and Ahringer, Essential genes 2001). Redundant pathways, in which different processes can accomplish the same essential function, are more cryptic and are not likely to be detected except by fortuitous double mutant combinations or screens for synthetic lethal mutations (enhancers).…”
Section: Redundancy Of Essential Genesmentioning
confidence: 99%